Teacher... (Journal of Parents and Teachers, 2014)
In the following article, a poem dedicated to the teaching profession appears. In it, the qualities of a good teacher are reflected, as well as those tasks that we must fulfill as teachers for our students.
Keywords: sweetness; teacher; poem; students; pupils